Respon Akar Bibit Aren Genjah (Arenga pinnata) Di Pembibitan Pada Pemberian Dosis dan Interval Pupuk Organik Cair Nasa - Yetti Elidar (Universitas Widya Gama Mahakam, 2018)
Research on the response of roots of palm sugar palm seeds (Arenga pinnata) in nurseries at doses and intervals of Nasa liquid organic fertilizer. Aims to determine the dosage, interval and combination of dosages and fertilization intervals with Nasa liquid organic fertilizer which can provide the best dry weight of the roots in the nursery. The research design used was a Completely Randomized Design (CRD) with 3x3 factorial experiments and each treatment was repeated 8 (eight) times, consisting of: the first factor was the treatment of POC Nasa dose in a concentration of 3 cc POC Nasa per liter of water (D) consists of 3 levels, namely: d1 = 300 ml POC Nasa, d2 = 400 ml POC Nasa, d3 = 500 ml POC Nasa, while the second factor is the treatment of POC Nasa Interval (I) consisting of 3 levels, namely: i1 = 2 once a week, i2 = once every 3 weeks, i3 = once every 4 weeks. The results of the POC Nasa dose study had a significant effect on leaf wet weight, leaf dry weight, root wet weight and root dry weight. The best dose at this level are: d2 (400 ml of Nasa liquid organic fertilizer), the interval of liquid organic fertilizer Nasa has a significant effect on leaf wet weight, leaf dry weight, root wet weight and root dry weight. The best dose at this level is: i1 (once every 2 weeks). The treatment combination has no significant effect on all parameters.